Human Needs, Robotic Means: Capitalist Ideals in Ishiguro’s Klara and the Sun - Adhikari, Chulendra; Pokharel, Bishnu Prasad (SNPRC Journal, 2024)
The purpose of this study is to explore the way Kazuo Ishiguro's Klara and the Sun (2021) depicts as an ongoing transaction between human beings and artificial intelligence (AI), blurring the hierarchy between human beings and machines in the capitalist society. Karl Marx's commodification is a critical theoretical lens to critically analyze the theme and characters and critically scrutinizes how Klara, a solar-powered robot, an artificial friend, Josie, Rick, and Melania become the subject of commodity and lose their self in the human society. Through rigorous analysis, it infers the way characters’ position is reduced to the objects of market value and social capital. Their conversion into consumer products for transactions is the core epitome of the analysis. Klara is a commodity to fulfil her family expectations and demands, but she is ignored and disposed at the end, whereas Josie is 'genetically engineered' for academic excellence and a better career, whose value is judged based on social benefits, relations, and utility. Rick is treated as less human due to the lack of his genetic modification, whereas Melania's voice is switched off as she performs the role of a housekeeper. Taking a lead from the above argument, this research paper concludes that the value of human beings and artificial objects is shaped by the buyer-seller relationship. Ultimately, humans and non-humans undergo commodification in the capitalist world.